2/17 + 17/2 + 15/17
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=(-5)+(-17)+(-15)+(-17)-17-(-2)
=>A=-5-17-15-17-17-2
=>A= -(5+17+15+17+17+2)
=> A= -73
(217 + 172).(915 - 315).(24 - 42)
= (217 + 172).(915 - 315).(16 - 16)
= (217 + 172).(915 - 315).0
= 0
ta có:\(A=\frac{17^{15}+3}{17^{15}-2}=\frac{17^{15}-2+5}{17^{15}-2}=\frac{17^{15}-2}{17^{15}-2}+\frac{5}{17^{15}-2}=1+\frac{5}{17^{15}-2}\)
\(B=\frac{17^{15}}{17^{15}-5}=\frac{17^{15}-5+5}{17^{15}-5}=\frac{17^{15}-5}{17^{15}-5}+\frac{5}{17^{15}-5}=1+\frac{5}{17^{15}-5}\)
vì 1715-2>1715-5
=>\(\frac{5}{17^{15}-2}<\frac{5}{17^{15}-5}\)
=>A<B
Lời giải chi tiết:
12 – 2 < 11 | 13 > 17 – 5 | 18 – 8 = 11 – 1 |
15 – 5 < 15 | 17 > 19 – 5 | 17 – 7 = 12 – 2 |
a,-5/9 + 8/18 + -2/11 + 4/-9 + 7/15 b,5/17 + -9/15 + -2/17 + 2/5 + 14/17
= -5/9 + 4/9 + -2/+ 4/-9 + 7/15 = 5/17 + -3/5 + -2/17 + 2/5 + 14/17
=(-5/9 + 4/9 + -4/9 ) +-2/11 + 7/15 = ( 5/17 + -2/17 + 14/17) + ( 2/5 + -3/5)
= -1/3 + -2/11 + 7/15 =1 + -1/5
=-75/225 + -30/ 225 + 77/225 =4/5
= -25/225 = -1/9 ( 4/5 = 0.8 )
\(=\dfrac{15}{17}\left(\dfrac{45}{33}-\dfrac{12}{33}\right)=\dfrac{15}{17}\)
19/2!!!!!!!!!!!!!!
\(\frac{2}{17}+\frac{17}{2}+\frac{15}{17}\)
\(=\left(\frac{2}{17}+\frac{15}{17}\right)+\frac{17}{2}\)
\(=1+\frac{17}{2}\)
\(=\frac{19}{2}\)